Changes of an injured fornix in a patient with mild traumatic brain injury: Diffusion tensor tractography follow-up study. (October 2014) - Lee, Han Do; Jang, Sung Ho
Abstract Background: This study investigated the changes of an injured fornix from early stage to chronic stage in a patient with mild traumatic brain injury (TBI), using diffusion tensor tractography (DTT). Methods: A 25-year-old female suffered from head trauma resulting from a pedestrian car accident. The patient showed a total score of 86 for memory impairment on the Memory Assessment Scale at 2 weeks after onset; however, her memory has been recovered to within normal range, with a score of 105 at 9 months after onset. Results: The middle portion of the right fornical crus showed narrowing and the discontinued left fornical crus was shortened on 9-month DTT compared with 2-week DTT. Two branches from the right fornical column and body were observed on 9-month DTT; in contrast, the two branches from the left fornical column and the left fornical body were elongated and shortened, respectively, on 9-month DTT compared with 2-week DTT. Conclusions: The narrowed lesion in the middle of the right fornical crus and the shortening of the discontinued left fornical crus appear to indicate degeneration following traumatic axonal injury. In contrast, the neural branches from both fornices appear to be related to the functional recovery mechanisms of the injured fornix.